Introduksi Pangan Lokal pada Produk Olahan Ikan sebagai Upaya Peningkatan Daya Saing - Yohana Sutiknyawati Kusuma Dewi; Oke Anandika Lestari; Widadi Padmarsari Soetignya (Jurnal Pengabdian Pada Masyarakat, 2019)
LOCAL FOOD INTRODUCTIONS INTO FISH PROCESSED PRODUCT AS A WAY TO ENHANCE COMPETITIVE VALUE. Bilayuk Village is one of 18.25% underdeveloped village with IDM (Village Development Index) score below 0.491. Based on Forum Group Discussion results with village officials, one of the main reasons is the village’s human resources lack of knowledge. The lack of human resources knowledge leads to unutilised village’s local food. The abundant and unutilised local foods are tubers and san-sankng leaves. The tuber has potential as filling agent to reduce the amount of fish use in fish processed product, and san-sankq leaves can be used as flavour enhancer substitute (MSG). Therefore, in this community service activity, we provide training and assistance to fish cultivators in Bilayuk village to process the harvest into hekeng which enriched with tubers filling and used san-sankq leaves for seasoning. The purpose of the activity is to increase local competitive value of Bilayuk village with increasing knowledge in fish processing by processed it into hekeng made from local food. The results showed that there is increasing knowledge since audience never made hekeng and processing food without flavour enhancer before, 77% target audience understand how to make hekeng, 22% target audience really like the result, and the rest of the audience just like the result. All audience are practising how to make hekeng for their family consumption. The audience are expected to have interest to make hekeng to increase their family income.